2015
DOI: 10.1007/s00426-015-0734-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distinct magnitude systems for symbolic and non-symbolic number

Abstract: Cognitive models of magnitude representation are mostly based on the results of studies that use a magnitude comparison task. These studies show similar distance or ratio effects in symbolic (Arabic numerals) and non-symbolic (dot arrays) variants of the comparison task, suggesting a common abstract magnitude representation system for processing both symbolic and non-symbolic numerosities. Recently, however, it has been questioned whether the comparison task really indexes a magnitude representation. Alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 48 publications
12
67
0
2
Order By: Relevance
“…Thus, taken altogether, our results are in line with the dual-representation view, according to which symbolic and non-symbolic processing rely on two distinct number magnitude representations; symbolic numbers activating an exact number representation and non-symbolic numerosities the ANS [22]. Indeed, the unique representation view anticipated a similar increase of performance in symbolic and non-symbolic magnitude processing after both symbolic and non-symbolic conditions, which is not what we observed.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, taken altogether, our results are in line with the dual-representation view, according to which symbolic and non-symbolic processing rely on two distinct number magnitude representations; symbolic numbers activating an exact number representation and non-symbolic numerosities the ANS [22]. Indeed, the unique representation view anticipated a similar increase of performance in symbolic and non-symbolic magnitude processing after both symbolic and non-symbolic conditions, which is not what we observed.…”
Section: Discussionsupporting
confidence: 82%
“…According to this view, both symbolic and non-symbolic magnitude comparisons show ratio effects [11, 17, 18] and similar brain areas would be activated for both types of stimuli ([1921], see [2, 17] for a review). These studies suggest that symbolic and non-symbolic magnitude processing activate one approximate magnitude representation system, the ANS [22]. Finally, the unique-representation view postulates that the ANS underlies math learning [13, 23] as ANS acuity has been shown to correlate with individual differences in mathematics competences [15, 24] and to be lower in people presenting specific math learning disability or dyscalculia [25–27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it appears that numerical ordering skills become particularly important from around the age of 6 or 7 (Attout & Majerus, ; Lyons, Price, Vaessen, Blomert, & Ansari, ; Sasanguie & Vos, ), there is also now emerging evidence in support of a role of nonnumerical ordering in mathematical development in the case of younger children (Attout, Noël, & Majerus, ; Morsanyi, van Bers, O'Connor, & McCormack, ; O'Connor, Morsanyi, & McCormack, ). Nonnumerical order processing measures can be broadly divided into two categories: those involving the retrieval of a familiar sequence from long‐term memory, such as the order of familiar daily events, familiar everyday sequences, the months of the year, or letters (Morsanyi, O'Mahony, & McCormack, ; O'Connor et al, ; Sasanguie, De Smedt, & Reynvoet, ; Vos, Sasanguie, Gevers, & Reynvoet, ), and those involving the retrieval of a novel, arbitrary sequence from short‐term memory (order working memory [WM] task; Attout & Majerus, , ; Attout et al, ). O'Connor et al () found that both numerical and nonnumerical ordering measures were related to early mathematical achievement in 4–5‐year‐old children.…”
Section: Table Showing the Results Of Three Longitudinal Studies Regamentioning
confidence: 99%
“…The task is based on Sasanguie and Reynvoet (; see also Sasanguie, De Smedt, et al. ). Participants heard a number word (range: 1–9) and simultaneously a dot array was visually presented on a computer screen.…”
Section: Methodsmentioning
confidence: 99%